STRATEGIES USED TO REDUCE RISK IN BUSINESS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Every entrepreneurial activity begins with the creation of a business plan and risk calculation. Business risk is the risk of losses and loss of income as a result of certain management decisions related to financial and economic activities. When starting a business, the manager tries to “catch” the balance between profit and loss reduction. To achieve a positive economic result, he must consciously make a risky decision. This article focuses on examining business risks to withstand negative impacts in the future. An algorithm to reduce some types of risks is also proposed.